(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article examines effective and practical methods and approaches used in teaching foreign languages from a theoretical and pedagogical perspective. It focuses on the communicative approach, task-based learning, interactive teaching methods, information and communication technology (ICT)-based instruction, and integrative teaching strategies. Special attention is given to the pedagogical foundations of these methods, their impact on developing learners’ linguistic and communicative competence, and their role in improving overall educational outcomes. The study also highlights the importance of the teacher’s role, student engagement, and innovative methodologies in modern language education. The findings indicate that a balanced combination of various teaching approaches significantly enhances the effectiveness of foreign language instruction.